Association between social conditions and oral health in school failure - Inara Pereira da Cunha; Antonio Carlos Pereira; Marcelo de Castro Meneghim; Antônio Carlos Frias; Fábio Luiz Mialhe (Universidade de São Paulo, 2019)
ABSTRACT OBJECTIVE To evaluate the association of school failure among Brazilian adolescents with social conditions and aspects of oral health through hierarchical analysis. METHODS A state-wide survey of 5,558 adolescents from the state of São Paulo, Brazil, inquired about the sociodemographic and social capital of participants by using a structured questionnaire. Trained and calibrated professionals performed intraoral examinations and interviews in the households. Questions about the access to dentist, reason for and frequency of using dental services, toothache episodes and impact of oral conditions on daily activities (OIDP) were applied. Oral examinations evaluated caries experience, tooth losses, periodontal problems, presence of open bite, and maxillary and mandibular overjet. School failure was estimated according to the teenagers' years of schooling. The independent variables were grouped into three blocks: sociodemographic and economic characteristics, social capital and oral health aspects. The multiple hierarchical logistic regression model was used to identify the factors associated with school failure. RESULTS Of the total sample, information about schooling of 5,162 adolescents was obtained, of whom 29.6% presented school failure. We found that adolescents over the age of 16 years who did not declare themselves as white, female, with feelings of insecurity, unhappiness, with toothache, caries, tooth losses, affected by dentofacial and/or periodontal changes, were more likely to fail at school. CONCLUSION Oral disorders and social factors were associated with school failure in adolescents. A successful school trajectory was a strong determinant of health, therefore actions between the educational and health sectors must be developed for adolescents, especially those with this profile.